EVOLUTION OF SCIENTIFIC APPROACHES TO HUMAN RESOURCE MANAGEMENT IN AGRICULTURAL ENTERPRISES UNDER CONDITIONS OF INNOVATIVE TRANSFORMATIONS (INNOVATIVE ECONOMY, 2026)
Staruk T.M. EVOLUTION OF SCIENTIFIC APPROACHES TO HUMAN RESOURCE MANAGEMENT IN AGRICULTURAL ENTERPRISES UNDER CONDITIONS OF INNOVATIVE TRANSFORMATIONSPurpose. The aim of the article is to examine the evolution of scientific approaches to human resource management in agricultural enterprises in the context of innovative transformations and to substantiate their role in ensuring the efficiency of enterprise performance.Methodology of research. The theoretical and methodological basis of the study is the systems approach to the analysis of social and economic processes and phenomena. The following methods were used in the course of the research: the abstract and logical method – to examine the evolution of scientific approaches to human resource management in agricultural enterprises; the method of generalization – to systematize theoretical approaches, identify their essential characteristics, instruments and limitations, and to formulate the conclusions of the study.Finding. The necessity of taking into account the specific features of innovative transformations in the process of human resource management in agricultural enterprises is substantiated. Scientific approaches to human resource management are systematized into five groups: administrative, economic, behavioural, strategic, and innovative. For each approach, the essential characteristics, instruments, and limitations are identified, which made it possible to generalize their capabilities and limits of application under modern conditions of enterprise functioning.Originality. The author’s approach to considering the specifics of innovative transformations in human resource management at agricultural enterprises was developed, based on the differentiated identification of the features of transformations, as well as the prevailing instruments and limitations within each of the identified approaches. This makes it possible to more substantively determine the directions for improving human resource management under modern conditions of enterprise performance. Practical value. The obtained research findings can be used to improve approaches to human resource management, personnel policy formation, the selection of management instruments, and the development of human resource management systems in agricultural enterprises.Key words: human resources, agricultural enterprises, management, theoretical approaches, innovative transformations, evolution.
Keywords: human resources; agricultural enterprises; management; theoretical approaches; innovative transformations; evolution